2018
DOI: 10.1074/jbc.ra118.003784
|View full text |Cite
|
Sign up to set email alerts
|

The extreme C terminus of the Pseudomonas aeruginosa effector ExoY is crucial for binding to its eukaryotic activator, F-actin

Abstract: Edited by Velia M. FowlerBacterial nucleotidyl cyclase toxins are potent virulence factors that upon entry into eukaryotic cells are stimulated by endogenous cofactors to catalyze the production of large amounts of 35-cyclic nucleoside monophosphates. The activity of the effector ExoY from Pseudomonas aeruginosa is stimulated by the filamentous form of actin (F-actin). Utilizing yeast phenotype analysis, site-directed mutagenesis, functional biochemical assays, and confocal microscopy, we demonstrate that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 46 publications
2
13
0
Order By: Relevance
“…Our data show that ExoY is a monomer in solution, and a previous mutational study suggested that ExoY possesses only one F-actin-binding region, the C-terminal end of ExoY (5). We therefore hypothesize that ExoY likely dimerizes to promote F-actin bundling, a mechanism commonly used by many cellular F-actin-bundling or crosslinking proteins, as discussed above.…”
Section: Exoy Induces F-actin Bundlingsupporting
confidence: 71%
See 1 more Smart Citation
“…Our data show that ExoY is a monomer in solution, and a previous mutational study suggested that ExoY possesses only one F-actin-binding region, the C-terminal end of ExoY (5). We therefore hypothesize that ExoY likely dimerizes to promote F-actin bundling, a mechanism commonly used by many cellular F-actin-bundling or crosslinking proteins, as discussed above.…”
Section: Exoy Induces F-actin Bundlingsupporting
confidence: 71%
“…ExoS and ExoT both exhibit G-protein activating and ADP-ribosylation activities, whereas ExoU is a potent phospholipase (4). ExoY is a promiscuous nucleotidyl cyclase that has recently been demonstrated to be activated by binding to actin filaments (F-actin), but not globular actin (G-actin) (5)(6)(7)(8).…”
mentioning
confidence: 99%
“…After activation, the toxin generates a supraphysiologic amount of 207 cGMP and cAMP that impedes cell signaling. It was previously demonstrated that the 208 mutagenesis of D25 in actin abolishes ExoY binding to F-actin (Belyy et al, 2018). The same 209 actin mutation also prevents Lifeact binding, we therefore hypothesize that Lifeact and ExoY 210 have overlapping binding sites.…”
Section: Lifeact Mutations Increase Its Affinity To F-actin 156mentioning
confidence: 56%
“…After activation, the toxin generates a supraphysiologic amount of 3′,5′-cyclic guanosine monophosphate (cGMP) and 3′,5′-cyclic adenosine monophosphate (cAMP) that impedes cell signaling. The mutagenesis of D25 in actin abolishes ExoY binding to F-actin [ 35 ]. Since the same actin mutation also prevents Lifeact binding, we hypothesize that Lifeact and ExoY have overlapping binding sites.…”
Section: Resultsmentioning
confidence: 99%